Combined Drainage and Protocolized Necrosectomy Through a Coaxial Lumen-apposing Metal Stent for Pancreatic Walled-off Necrosis: A Prospective Multicenter Trial. Issue 5 (6th May 2023) - Dayyeh, Barham K. Abu; Chandrasekhara, Vinay; Shah, Raj J.; Easler, Jeffrey J.; Storm, Andrew C.; Topazian, Mark; Levy, Michael J.; Martin, John A.; Petersen, Bret T.; Takahashi, Naoki; Edmundowicz, Steven; Hammad, Hazem; et al.
Abstract : Objective: We evaluated a protocolized endoscopic necrosectomy approach with a lumen-apposing metal stent (LAMS) in patients with large symptomatic walled-off pancreatic necrosis (WON) comprising significant necrotic content, with or without infection. Summary Background Data: Randomized trials have shown similar efficacy of endoscopic treatment compared with surgery for infected WON. Design: We conducted a regulatory, prospective, multicenter single-arm clinical trial examining the efficacy and safety of endoscopic ultrasound -guided LAMS with protocolized necrosectomy to treat symptomatic WON ≥6 cm in diameter with >30% solid necrosis. After LAMS placement, protocolized WON assessment was conducted and endoscopic necrosectomy was performed for insufficient WON size reduction and persistent symptoms. Patients with radiographic WON resolution to ≤ 3 cm and/or 60-day LAMS indwell had LAMS removal, then 6-month follow-up. Primary endpoints were probability of radiographic resolution by 60 days and procedure-related serious adverse events. Results: Forty consecutive patients were enrolled September 2018 to March 2020, of whom 27 (67.5%) were inpatients and 19 (47.5%) had clinical evidence of infection at their index procedure. Mean WON size was 15.0 ± 5.6 cm with mean 53.2% ± 16.7% solid necrosis. Radiographic WON resolution was seen in 97.5% (95% CI, 86.8%, 99.9%) by 60 days, without recurrence in 34 patients with 6-month follow-up data. Mean time to radiographic WON resolution was 34.1 ± 16.8 days. Serious adverse events occurred in 3 patients (7.5%), including sepsis, vancomycin-resistant enterococcal bacteremia and shock, and upper gastrointestinal bleeding. There were no procedure-related deaths. Conclusions: Endoscopic ultrasound-guided drainage with protocolized endoscopic necrosectomy to treat large symptomatic or infected walled-off necrotic pancreatic collections was highly effective and safe. Clinicaltrials.-gov no: NCT03525808.